Compliance of Nurses with Hand Hygiene Guidelines in Tripoli University Hospital, 2019 - Jerbi, Rehab S.; Said, Amal I.; Elhamadi, Miluda R. (Ibnosina Journal of Medicine and Biomedical Sciences, 2022)
Background Health care-associated infections (HAIs) result in high morbidity, decreased personal satisfaction, and mortality. Implementing infection prevention and control strategies such as hand hygiene (HH) promotion is critical to reduce the risk of the HAI and protect patients.Aims This study aimed to determine the compliance rate of HH among nurses in Tripoli University Hospital (TUH, previously known as Tripoli Medical Center).Method A cross-sectional study was conducted in different departments at TUH, starting from May 1st to October 31st, 2019. An observational checklist based on the “five moments for hand hygiene” of World Health Organization (WHO) was used. There were 271 nurses who interacted with 1,213 patients, a total of 3,452 HH episodes, and 6,065 cases of HH that were collected in this study, and data were statistically analyzed.Results The overall HH compliance rate was 56.9%. Most of the nurses (86%) preferred to use HH after contact with individual patients and 71.6% after contact with patients' environment. There was, however, low percentage of HH prior to patient contact (35.1%). The compliance rate was higher among nurses of the age group of less than 20 years (60.8%), non-Libyan (60.7%), and those who received formal training (60.5%).Conclusion In general, the HH compliance rate was low among nurses working in TUH. Education is an important factor that impacts the practice of HH pre- and postpatient contact. Wider studies that include assessment of pre- and posteducation courses should be conducted in the future.
Keywords: hand hygiene; compliance; nurses; Tripoli University Hospital